2010
DOI: 10.1242/jcs.070508
|View full text |Cite
|
Sign up to set email alerts
|

A role for the dynamin-like protein Vps1 during endocytosis in yeast

Abstract: SummaryDynamins are a conserved family of proteins involved in membrane fusion and fission. Although mammalian dynamins are known to be involved in several membrane-trafficking events, the role of dynamin-1 in endocytosis is the best-characterised role of this protein family. Despite many similarities between endocytosis in yeast and mammalian cells, a comparable role for dynamins in yeast has not previously been demonstrated. The reported lack of involvement of dynamins in yeast endocytosis has raised questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 55 publications
(78 reference statements)
5
76
0
Order By: Relevance
“…6E). Such repetitive densities have been observed in wild-type cells previously (Smaczynska-de Rooij et al, 2010). In our hands these densities were only clearly visible in the cap1 Δ knockout strain, possibly due to accumulation of endocytic invaginations in a specific stage of internalization.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…6E). Such repetitive densities have been observed in wild-type cells previously (Smaczynska-de Rooij et al, 2010). In our hands these densities were only clearly visible in the cap1 Δ knockout strain, possibly due to accumulation of endocytic invaginations in a specific stage of internalization.…”
Section: Resultssupporting
confidence: 80%
“…1D), as we described previously (Kishimoto et al, 2011). In wild-type cells the membrane invaginates perpendicularly to the plasma membrane with less than 30° deviation (Smaczynska-de Rooij et al, 2010; Kishimoto et al, 2011). The constriction of the tubule region brings the opposing membranes within fusion range and at the same time creates the lumen of the future endocytic vesicle.…”
Section: Resultsmentioning
confidence: 99%
“…In alpha facor arrested cells, Vps1 interacts with the septins (Renz et al, 2016). Vps1 is a dynamin related protein that functions at several stages of membrane trafficking including endocytic scission (Smaczynska-de Rooij et al, 2010, 2015). …”
mentioning
confidence: 99%
“…In other studies we have observed abnormal endocytic phenotypes caused by vps1 alleles in cells that appear to carry out other Vps1 functions appropriately 253340. We therefore aimed to determine whether any of the disease mutations were able to affect the progression of individual endocytic events.…”
Section: Resultsmentioning
confidence: 96%
“…Self assembly assays: method adapted from 25. 10 µM Vps1 (or mutant variant) was added to liposome buffer at the concentrations shown and centrifuged at 313,000g for 15 min to remove any aggregated protein.…”
Section: Methodsmentioning
confidence: 99%